Предмет: Алгебра,
автор: annatotoeva
докажите тождество (m²+1)(n²+1)=(mn-1)²+(n+m)
Ответы
Автор ответа:
0
(m²+1)(n²+1)=(mn-1)²+(n+m)²
m²n²+m²+n²+1=m²n²-2mn+1+n²+m²+2mn
m²n²+m²+n²+1=m²n²+m²+n²+1
============================
левая и правая равны
у вас неправильно написано Вы квадрат пропустили
m²n²+m²+n²+1=m²n²-2mn+1+n²+m²+2mn
m²n²+m²+n²+1=m²n²+m²+n²+1
============================
левая и правая равны
у вас неправильно написано Вы квадрат пропустили
Похожие вопросы
Предмет: Математика,
автор: milentes
Предмет: Математика,
автор: mamedovafelis21
Предмет: Математика,
автор: Pennoo
Предмет: Алгебра,
автор: minija
Предмет: Алгебра,
автор: Anni0Ni